Biased Technological Progress and Labor Force Growth in a Dualistic Economy - Kelley, Allen C.; Williamson, Jeffrey G.; Cheetham, Russell J. (Quarterly Journal of Economics, 1972)
Introduction, 426. — I. The structure of the dual economy, 427. — II. Labor force growth and biased technological progress: comparative statics, 432. — III. Labor force growth and biased technological progress: dynamics, 435. — IV. A numerical experiment, 436. — V. Conclusion, 443. —Appendix A, 445. — Appendix B, 447.